Clinical Correlations of Biomarkers in Chronic Heart Failure Developed on the Background of Rheumatic Heart Disease - Sulaymonovna, Khatamova Raykhon (American Journal of Biomedicine and Pharmacy, 2025)
With the increase in life expectancy worldwide, the prevalence and incidence of chronic heart failure (CHF) and cardiovascular diseases (CVD) are also rising. It is well known that CHF and renal dysfunction frequently coexist as comorbid conditions, contributing to the development of adverse outcomes in the cardiovascular continuum and increasing mortality [202, 61, 36, 1]. CHF has a pronounced negative impact on renal and glomerular hemodynamics. In recent years, many literature reviews have emphasized the interrelationship between the heart and kidneys, described by the term "cardiorenal syndrome," which encompasses complex mechanisms of pathophysiological changes.